New taxa and new records of Deltocephalini leafhoppers from Thailand (Hemiptera: Cicadellidae: Deltocephalinae) - Duan, Yani; Dietrich, Christopher H.; Webb, Michael D.; Zhang, Yalin (Zootaxa, 2017)
Two new genera and three new species of the leafhopper tribe Deltocephalini are described from Thailand, viz., Loeia Duan gen. n. with L. tamtipi Duan sp. n. as type species, Phetchabunia Duan gen. n. with P. janteabi Duan sp. n. as type species, and Maiestas subsirii Duan sp. n.. Five new country records for Thailand are also given, viz. Deltocephalus vulgaris Dash & Viraktamath, Maiestas dinghuensis Zhang & Duan, Maiestas scripta (Distant), Paramesodes sp., and Polyamia acicularis Dai, Xing & Li.